STEM ANATOMY OF THREE PINANGA SPECIES FROM ASSAM OF NORTHEAST INDIA - Selim Mehmud; Himu Roy (Indonesian Journal of Forestry Research, 2023)
The stem anatomy of the genus Pinanga Blume distributed to Assam of northeast India remains unattended. An anatomical study was conducted to address this research gap, where the plant samples to Pinanga were collected from different parts of Assam and identified as P. gracilis, P. griffithii, and P. sylvestris. The findings recorded anatomical variation among the species. Freehand sections of the stems were conducted, double-stained, quality specimens mounted, and suitable slides were observed under a light microscope. The types of epidermal cells and metaxylem vessels were variable among the studied species. In this study, vascular bundles with more than one metaxylem vessel were also recorded, which can be used for identification.